2003
DOI: 10.1177/1077559503258930
|View full text |Cite
|
Sign up to set email alerts
|

Substantiation and Recidivism

Abstract: This article reports rates of recidivism among initially substantiated and initially unsubstantiated child maltreatment events to determine if substantiation status is associated with higher risk of recidivism. This is an important question given recent concerns that unsubstantiated cases may have as high or almost as high a risk of recidivism as do substantiated cases. The data are analyzed at both the victim level and the case level, divided by type of maltreatment, and followed for 4.5 years. The data used … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

22
157
3
3

Year Published

2007
2007
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 239 publications
(185 citation statements)
references
References 20 publications
22
157
3
3
Order By: Relevance
“…[108][109][110][111][112][113] The reported recurrence rate increased to between 40% and 80% in studies looking at high-risk children, or an extended time at risk, or in studies with a low threshold for recording abuse. 54,112,114,115 Only a minority of repeated episodes of suspected abuse were substantiated 116 or referred to social services, 117 and few attended hospital. In a randomised controlled trial of home visiting for children with substantiated physical abuse conducted in Canada, 47% of 160 children followed for 3 years had at least one recurrent physical abuse event but none of these children attended hospital.…”
Section: Review Resultsmentioning
confidence: 99%
“…[108][109][110][111][112][113] The reported recurrence rate increased to between 40% and 80% in studies looking at high-risk children, or an extended time at risk, or in studies with a low threshold for recording abuse. 54,112,114,115 Only a minority of repeated episodes of suspected abuse were substantiated 116 or referred to social services, 117 and few attended hospital. In a randomised controlled trial of home visiting for children with substantiated physical abuse conducted in Canada, 47% of 160 children followed for 3 years had at least one recurrent physical abuse event but none of these children attended hospital.…”
Section: Review Resultsmentioning
confidence: 99%
“…It should be emphasized that according to the harm/ evidence model of substantiation, a substantiated report is not equivalent to verifying the presence of maltreatment but rather a label used when sufficient evidence and/or risk of harm exists to permit family court intervention if needed. [18] In Missouri, both substantiated and unsubstantiated cases have been eligible to receive in-home or foster care intervention for many years. RPS cases are not cases that are "bogus" or refused for investigation but includes serious family problems like homelessness that require referrals but do not rise to the legislative standard for abuse and neglect.…”
Section: Official-report Maltreatment/foster Datamentioning
confidence: 99%
“…Despite substantial research documenting the relative equivalent risk for unsubstantiated or substantiated reports of child maltreatment [18][19][20][21][22], a records purge cycle was enacted by law in 2003, which mandated the purging of any unsubstantiated case without recurrence or service within 3 years and any substantiated cases without recurrence or services within 10 years. In other words, either the subsequent receipt of formal service or a recurrence before the purge date extends the retention period for the record.…”
Section: Official-report Maltreatment/foster Datamentioning
confidence: 99%
“…Cases that return to the attention of child welfare are of major concern because they represent a short-or long-term lack of protection, are costly, and are associated with negative long-term developmental outcomes for the children. Depending on the length of follow-up, studies have found rates of rereport to be in the 30% to 60% range (DePanfilis, 1995;DePanfilis & Zuravin, 1998;Drake et al, 2003;English et al, 2002;Fryer & Miyoshi, 1994). Predictably, those studies that feature longer follow-up periods (e.g., Drake et al, 2003) show higher rates.…”
Section: Substantiation and Future Harmmentioning
confidence: 99%